A coupled electrical-thermal impedance matching model for design optimization of thermoelectric generator - He, Zhi-Zhu (Applied energy, 2020)
•A fast and accurate 1D self-consistent numerical method was developed for TEG couple.•A coupled electrical-thermal impedance matching model was developed.•The explicit single or two-parameter geometry optimization models were derived.•The impacts of the asymmetric external thermal resistance were demonstrated. Based on the definition of numerical-type equivalent thermoelectric parameters through developing a 1D self-consistent numerical method, this paper established a novel coupled electrical-thermal impedance matching (CETIM) model for prediction of the maximum output power and the highest conversion efficiency of thermoelectric generator (TEG). CETIM model could highlight the impacts of thermal working conditions and temperature-dependent properties on the TEG performance. It also clarifies the unreasonable assumption of the impedance matching conditions in the literature, which would lead to underestimation by 10.9% for the maximum output power prediction under a large thermal resistance between TEG and heat reservoirs. The analytical expressions of the output power and conversion efficiency obtained through CETIM model were used to derive the single- and two-parameter geometry optimization models, which could be quickly and accurately solved without needing the complicated optimization methods. It is found that the two-parameter optimization model could lead to a higher output power compared with that based on the single-parameter model, such as the observed improvement by 27.8% for the maximum output power and 21.6% for the corresponding conversion efficiency, respectively. Impacts of the coupled thermal-electrical working conditions and geometric sizes on the TEG performance were also investigated in detail. The results indicated that decreasing the thermal resistance between TEG and heat sink could acquire a larger output power and conversion efficiency compared with that through reducing the thermal resistance between TEG and heat source, such as increase by 15% for the output power and by 4% for the conversion efficiency, respectively. The present study provides an accurate and time-efficient comprehensive modeling tool for geometric optimization of TEG, which was implemented by MATLAB open source codes presented in supplementary materials.